9-11 yaş arası görme yetersizliği olan çocuklarda hareket eğitimi ve goalball eğitimlerinin öz-duyarlılık gelişimi üzerine etkilerinin değerlendirilmesi - Çakır, Güneş (My University, 2022)
Bu çalışmada hareket eğitimi ve goalball eğitimlerinin görme yetersizliği olan çocuklarda öz-duyarlılık gelişimleri üzerine etkilerinin değerlendirilmesi hedeflenmiştir. Bu amaçla 12 hafta boyunca görme yetersizliği olan çocuklarda hareket eğitimi ve goalball eğitimleri yapılmıştır. Araştırma kapsamına Türkan Sabancı Görme Engelliler okulu 9-11 yaş grubu öğrencilerinden yansız olarak atanan 30 öğrenci gönüllü olarak katılmıştır. Öğrenciler yansız olarak 3 gruba ayrılmıştır. Çalışmada Prof.Dr. Ahmet AKIN tarafından geliştirilmiş “Öz-Duyarlık Ölçeği” kullanılmıştır. Ölçek görme yetersizliği durumunda da kullanılabilir sorular içermektedir. Ölçek için gerekli izinler alınmıştır. Araştırma da ön test son test kontrol gruplu model uygulanmıştır. Görme engelli 30 çocuk üzerinde yapılan araştırmada; Goalball ve hareket eğitimi programlarının öz-duyarlılık gelişimine etkilerinin değerlendirilmesi ön test ve son test puanları arasında fark var mıdır? Goalball, hareket eğitimi ve kontrol gruplarının puanları arasında fark var mıdır? sorularına cevap aranmıştır. Veriler, SPSS (Statistical Package for Social Sciences) paket kullanılarak, analizler ham puanlar üzerinden gerçekleştirilmiştir. Araştırmada elde edilen bulgular: Çalışmaya katılan 9-11 yaş aralığındaki görme yetersizliği olan çocuklar, hareket eğitimi ve goalball uygulamaları öz-duyarlılık gelişimi üzerindeki etkileri karşılaştırıldığında gruplar arasında istatistiksel açıdan anlamlı bir farklılık tespit edilememiştir(p>0.05).

Evalation of the Effects of Movement Education and Goalball Training on Self- Awereness Development in Visually Impaired Children between Ages9-11 The aim of this study is to examine the effects of movement training and goalball training on the development of self-compassion in children with visual impairment. For this purpose, movement training and goalball training were given to children with visual impairment for 12 weeks. 30 students of 9-11 age group from Türkan Sabancı School for the Visually Impaired who were impartially assigned participated in the research voluntarily. The students were impartially divided into 3 groups. “Self-Compassion Scale” developed by Prof.Dr. Ahmet AKIN was used for the study. The scale includes questions which can also be used for assessing persons with visual impairment. Necessary permissions were obtained for the use of the scale. The pretest-posttest-control group model was appliedIn the research. In this study conducted on 30 visually impaired children; answers to the questions (1) Is there a difference between the pretest and posttest scores from evaluating the effects of goalball and movement training programs on the development of self-compassion? (2) Is there any difference between the scores of goalball training, movement training and control groups? were sought. The data were analyzed using the SPSS (Statistical Package for Social Sciences) package program, and the analyzes were performed on raw scores. Findings obtained in the study: When the effects of movement training and goalball training on the development of self-compassion were compared in children with visual impairment between the ages of 9-11 who participated in the study, no statistically significant difference was found between the groups (p>0.05).
Evalation of the effects of movement education and goalball training on self-awereness development in visually ımpaired children between ages9-11
Keywords: Children with visual disabilities; Fizyolojik yönleri; goalball hareket eğitimi Movement Education Goalball Training; Görme engelli çocuklar; Öz yapabilirlik (Psikoloji); Physiological aspects; Psikolojik yönleri; Psychological aspects; Self-actualization (Psychology); Social aspects; Sosyal yönleri; Spor; Spor, Çocuklar için; Sports